Business excellence model and its impact on organizational performance - Mohamad Azrol, Mohamad Dali (2016)
Business Excellence Model (BEM) was first introduced in Malaysia in the 90s by the Malaysia Productivity Corporation (MPC) through the Quality Management Excellence Award (QMEA) and Prime Minister Quality Award (PMQA) whereby the model is used as a criterion for the assessment of organization's excellence. Criteria contained in the model are referred to as the principles of Total Quality Management practices and also the criteria for the Malcolm Baldrige Excellence Award. The objective of this study is to examine the impact of Business Excellence program implementation with the practices of Business Excellence Model (BEM) on the organizational performance. Specifically, the study aims to analyze the relationship between the six dimensions of the BEM namely leadership, planning, information, customer, people and process with organizational performance. The samples in this study comprised of organizations that have been involved in the Business Excellence program and has been recognized as "Malaysia Productivity Innovation Class (MPIC)" by the Malaysia Productivity Corporation (MPC). Through statistical analysis conducted in this study, it was found that five dimensions in the Business Excellence Model have a positive and significant influence on the organizational performance. Discussions elaborated on the importance of Business Excellence Model in predicting organizational performance. Theoretical and practical implications, limitations, recommendations and conclusion are also brought to fore.